Effect of the city of Limón marine residual waters outfall discharges on water quality and phytoplankton abundance and diversity in the surroundings of Uvita Island, Costa Rica - Muñoz-Simon, Nelson (2020)
In order to assess the possible impact of the marine outfall of the city of Limón on the surrounding marine environment, six sampling stations were established, four near the vent zone and two controls. Water samples were taken in each station 0m and 10m deep during 2012- 2013 to measure nutrients, physicochemical parameters, microalgae concentration, and colony forming units (CFU) of Enterococcus. Microalgae abundance was compared between stations under outfall influence, their controls and depths using an analysis of similarities (ANOSIM). A SIMPER analysis was also conducted to determine species when significant differences were found. Phytoplankton abundance was also used to rank the dominance of species using the Olmstead-Tukey diagram and a canonical correspondence analysis. Results showed that in the area, there is a marked influence of rainfall on nutrients, silicate and orthophosphate, in addition to parameters such as dissolved oxygen and salinity. The dissolved oxygen concentration was high, reflecting that there is no significant organic load in the environment, while CFUs remained in ranges well below the maximum limits (35 UFC/100 mL) set by the United States Environmental Protection Agency (USEPA). Phytoplankton diversity was high and composed mostly of cosmopolitan species. Due to the low nutrient concentration and CFU counts, together with the high microalgae diversity, it is concluded that there is no direct evidence of a negative impact of the marine outfall on the studied area.